2018
DOI: 10.1103/physrevlett.120.067204
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Dyakonov-Perel-like Spin Relaxation in Pt

Abstract: We utilize nanoscale spin valves with Pt spacer layers to characterize spin scattering in Pt. Analysis of the spin lifetime determined from our measurements indicates that the extrinsic Elliot-Yafet spin scattering is dominant at room temperature, while the intrinsic Dyakonov-Perel mechanism dominates at cryogenic temperatures. The significance of the latter is supported by the suppression of spin relaxation in Pt layers interfaced with a ferromagnet, likely caused by the competition between the effective exch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 58 publications
10
21
0
Order By: Relevance
“…Our work provides strong evidence that ρ ⊥ determines λ s and hence it does not depend on t NM . In addition, we show evidence of the low influence of temperature in τ s of Pt, in agreement with recently reported results [11].…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our work provides strong evidence that ρ ⊥ determines λ s and hence it does not depend on t NM . In addition, we show evidence of the low influence of temperature in τ s of Pt, in agreement with recently reported results [11].…”
Section: Introductionsupporting
confidence: 93%
“…Moreover, the spin-flip scattering mechanisms that determine λ s are not completely understood. It has been generally assumed that the Elliot-Yaffet (EY) mechanism is the dominant mechanism in Pt; however, recent results have shown that both the Dyakonov-Perel (DP) and EY spin relaxation mechanisms coexist at low temperatures [11].…”
Section: Introductionmentioning
confidence: 99%
“…In Nb, the spin diffusion length has been estimated at λ Nb sd = 48 nm 47,86 . The spin diffusion length in Pt, λ Pt sd , is difficult to determine unambiguously because of the presence of SOC 98 , however the range of values is 1nm < λ Pt sd < 14nm [98][99][100] . Moreover, this spin diffusion length is expected to vary with the Pt layer thickness 100 .…”
Section: B Resultsmentioning
confidence: 99%
“…It is still an open question how the SSE current j s evolves for fast temperature variations and in the presence of nonthermal states. Insights into these points are crucial to reveal the role of elementary processes in the formation of the SSE current, for instance magnon creation 12 in F and spin relaxation 13 in N. The high-frequency behavior of the SSE is also relevant for applications, such as magnetization control by terahertz (THz) spin currents 14 16 and spintronic THz-radiation sources 17 21 .…”
Section: Introductionmentioning
confidence: 99%